Cognitive Behavior Therapy (CBT) sebagai Terapi Tingkat Depresi pada Lansia - Refina Anggraini; Wachidah Yuniartika (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of Cognitive Behavior Therapy (CBT) on reducing depression in older people in Gumpang Village. This research method uses a quantitative approach in the form of a pre-experiment with one-group pretest-post-design research conducted from November 2022 to December 2022. Respondents in this study were 87 elderly respondents in Gumpang Village, Kartasura District, Sukoharjo Regency. Respondents were taken using the Accidental Sampling Technique. Respondents were selected according to the discussion criteria as samples. Data collection used a research instrument in the form of a GDS-15 questionnaire with a total of 15 questions. The results of this study indicate that the p-value = 0.000 ≤ α = 0.05 (the p-value is smaller than α = 0.05). In conclusion, there are significant differences in depression before and after CBT therapy. Giving CBT has a substantial impact on reducing the level of depression in older people in Gumpang Village. Keywords: Depression, Elderly, Cognitive Therapy